2001
DOI: 10.1163/22941932-90000274
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Characteristics of Tension Wood and Opposite Wood in Young Inclined Stems of Poplar (Populus Euramericana Cv 'Ghoy')

Abstract: Young shoots from poplar cuttings (Populus euramericana cv ʻGhoyʼ) were artificially inclined to 30° from vertical to quantify the anatomical modifications induced by this gravitational stimulus. At the end of the growing season, the tension wood tissue (from the upper face of the inclined axis) was compared to the opposite wood tissue (from the lower face), with radial position taken into account. On isolated elements after maceration, fibres and vessels were significantly longer in tension wood tissue. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
92
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 26 publications
8
92
1
6
Order By: Relevance
“…There is no agreement in the literature regarding the length of tension wood fibres in comparison with that of normal fibres. Compared with normal fibres, tension wood fibres were reported sometimes as being longer [9,27,42], sometimes as being shorter (Giovanmi 1953, cited in Zimmermann [61]) and sometimes as having no marked difference [19,51]. In this study a very significant positive correlation (r = 0.751, significant at the 1% level) was found between fibre length and GSI values (Fig.…”
Section: Growth Stress/anatomical Propertiessupporting
confidence: 47%
See 3 more Smart Citations
“…There is no agreement in the literature regarding the length of tension wood fibres in comparison with that of normal fibres. Compared with normal fibres, tension wood fibres were reported sometimes as being longer [9,27,42], sometimes as being shorter (Giovanmi 1953, cited in Zimmermann [61]) and sometimes as having no marked difference [19,51]. In this study a very significant positive correlation (r = 0.751, significant at the 1% level) was found between fibre length and GSI values (Fig.…”
Section: Growth Stress/anatomical Propertiessupporting
confidence: 47%
“…However, Chow [9] reported that tension wood fibres were narrower than those of normal wood in beech on isolated fibres. Similarly, Wardrop [55] and Jourez et al [27] reported that in poplar (Populus alba and Populus euramericana cv. 'Ghoy', respectively), in the radial direction, the G-fibres were relatively narrower than the opposite wood fibres observed in cross-section.…”
Section: Growth Stress/anatomical Propertiesmentioning
confidence: 88%
See 2 more Smart Citations
“…In many angiosperms, including poplars (Jourez et al, 2001), the formation of reaction wood is characterized by the differentiation of a specific cellulose cell wall layer referred to as the G layer (Scurfield, 1973). Reaction wood formation is often accompanied by eccentric radial growth (Sinnott, 1952).…”
mentioning
confidence: 99%